THE EFFECT OF PH SOLUTIONS AND STIRRING SPEED ON NICKEL RECOVERY FROM PYROPHYLLITE ROCKS USING FROTH FLOTATION - Titi Pangesti Berlian Santoso; Sandra Santosa; Mas'udah Mas'udah (DISTILAT: Jurnal Teknologi Separasi, 2022)
Nickel is an important element in the metal alloy industry. In Indonesia, nickel resources are found in many areas in the form of rocks such as pyrophyllite. Froth flotation is a method commonly used in the mining industry to extract metals such as nickel from mineral rocks. However, the nickel concentrates yields tend to be relatively low. This is often influenced by several factors such as the pH solutions and stirring speed used in the process. Therefore, this study aims to investigate the effect of agitation speed and collector concentration on the nickel recovery results obtained from the froth flotation process. In this study, variations of pH solutions at 8,9, and 10 were used. Meanwhile, the stirring speed was varied to 700, 800 and 900 rpm. The results showed that the pH solutions and stirring speed had a significant impact on nickel recovery. Optimum results were obtained at pH of 10 and stirring speed of 900 rpm where the nickel concentration reached 27,55% from the initial concentration of 8,21%.